Future public service capacity: employment of young people into Australian public services during the GFC - Colley, Linda; Price, Robin (2015)
Public services face several workforce challenges, including impending retirements and austerity programs. Although employing more young people is a likely solution to balancing the demographic profile of public services, the literature and theory suggest that young people would have fared worse during the global financial crisis. This research tests propositions around the vulnerability of young people in selected Australian public services during the global financial crisis, in terms of quantity and quality of jobs obtained. Surprisingly, the findings suggest that many young people fared as well or sometimes better than other age cohorts during the global financial crisis in terms of both recruitment and access to ongoing jobs. There are several indications that perhaps public services provided a safe haven in a turbulent labour market. - Reproduced.
Keywords: Employment - Australia; Youth employment - Australia; Civil service - Australia; Civil service